(untitled) (Scholars’ Journal, 2020)
Language indexicality is the major problem in multilingual classrooms. Students from minority language communities may feel dominated in the classroom due to the lack of competency in the dominant languages used in the classroom. I have been dealing with such diversified classes for a long time and my teaching experience motivated me to carry out this research. This study tried to explore the nature of language dominance in a multilingual English language classroom and how students of minority community feel in the classroom. I used narrative inquiry as the main research design and purposive sampling procedure for sampling the participants and research site. Language dominance in the multilingual classroom was found problematic for minority community students. They mainly feel dominated in the classroom and do not enjoy studying in the classroom. The study also found that minority language learners are demotivated to take part in classroom interaction. Inappropriate use of dominating language by the teachers also found more problematic in the study. The study concluded that use of dominant language heavily in the multilingual classroom creates problem rather than helping those students who have different mother tongues.